2022
DOI: 10.1111/1759-7714.14635
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of switch/sucrose nonfermentable complex mutations with clinical outcomes in advanced non–small cell lung cancer

Abstract: Background: The switch/sucrose nonfermentable complex mutations (SWI/SNF-mut) are common in non-small cell lung cancer (NSCLC). However, the association of SWI/SNF-mut with the clinical outcomes of immune checkpoint inhibitors (ICIs), particularly of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), has not been established. Methods: We retrospectively collected data of patients at Cancer Hospital Chinese Academy of Medical Sciences. Patients with advanced NSCLC who received programmed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Results from a few studies suggested that NSCLC patients with a deficiency of SWI or SNF might be more sensitive to ICI treatment [ 109 , 110 , 112 , 113 , 114 , 115 , 117 ].…”
Section: Outcome Of Ici Treatment For Nsclc With Deficiency Of Swi/snfmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from a few studies suggested that NSCLC patients with a deficiency of SWI or SNF might be more sensitive to ICI treatment [ 109 , 110 , 112 , 113 , 114 , 115 , 117 ].…”
Section: Outcome Of Ici Treatment For Nsclc With Deficiency Of Swi/snfmentioning
confidence: 99%
“…It is noteworthy that all the listed studies were retrospective except for one case report. Results from a few studies suggested that NSCLC patients with a deficiency of SWI or SNF might be more sensitive to ICI treatment [109,110,[112][113][114][115]117].…”
Section: Outcome Of Ici Treatment For Nsclc With Deficiency Of Swi/snfmentioning
confidence: 99%